DIFFERENCES OF TOLERANCE CHARACTER PLANTING STRATEGIES RELIGIOUS INTEREST STUDENTS IN SDN INPRES 6.88 PERUMNAS 2 KOTA JAYAPURA - Rofiki, A. Arif; Amin, Muliaty; Susdiyanto, Susdiyanto; Yusuf T, Muh. (Jurnal Diskursus Islam, 2020)
This paper discusses the various strategies for cultivating thecharacter of inter-religious tolerance in students of SDN Inpres 6.88Perumnas 2 Kota Jayapura which is carried out through 1) schoolpolicies; 2) habituation to differences; 3) habituation to equations,and 4) group heterogeneity exercises. This research is field research. Theresearch approach used in this research includes methodological(phenomenological) and scientific approaches (normative, juridical, andpedagogical theological approaches). The research method used was aninterview, observation, and documentation. The results of this studyindicate that the character of interreligious tolerance in students of SDNInpres 6.88 Perumnas 2 Kota Jayapura is carried out through severalstrategies, namely: First, school policy. A strong commitment must bepossessed by school policymakers in cultivating the character of tolerancebetween religious believers in students. This commitment is manifested inthe inclusion of the character values of tolerance among religious believersin the mission, goals, and school regulations. Second, habituation todifferences. The teacher accustoms students to differences from an earlyage. This is done by giving understanding to students to appreciate thedifferences that exist between them. Besides, in learning the teacher alsotrains students to appreciate differences of opinion when discussing. Third, habituation to equality. The teacher gives the understanding that allstudents have the same position in a school that is, both become studentswho have the same rights and obligations. Students when learning areaccustomed to the teacher to see the similarities in meaning if there aredifferent answers. . The teacher invites students to think from the samepoint of view, not from each student. Fourth, exercise heterogeneity ingroups. The teacher gives group heterogeneity exercises to students inassigned group discussions during learning. The learning strategy used bythe teacher in group discussion assignments is the cooperative learningstrategy. Students work together in their study groups to complete theassignments the teacher has given them. Heterogeneity of study groups thatfavor cooperation can train and accustom students to learnto respect and tolerate differences that exist between themselves and theirpeers in terms of ethnicity, religion, social strata, or abilities.